Training for the use of cooperative applications in the Cooperative of the Republic of Indonesia (KP-RI) Mandiri Karangrejo Magetan Regency - Hedi Pandowo; Hamim Tohari; Qimyatussa’adah Qimyatussa’adah; Dian Kusumaningrum; Sugiharto Sugiharto (Journal of Community Engagement, 2025)
The Cooperative of the Republic of Indonesia (KP-RI) Mandiri Karangrejo Magetan Regency has an important role in managing finances and providing economic benefits for its members consisting of Civil Servants (PNS) and government employees with work agreements. The problem in this cooperative is that it has difficulty in maintaining good financial accountability because of the limitations in the use of information technology, which is still being recorded manually using the Microsoft Excel application and has not followed adjustments to the new regulation, namely the Minister of Cooperative Regulation No. 4 of 2024 This program aims to improve cooperative financial accountability through the implementation of information technology in the form of appropriate cooperative applications or software. The methods used include training in the use of software or cooperative applications and mentoring in the application of the system. The expected results are increasing accuracy and transparency in the management of cooperative finances, reporting formats and accounting policies in accordance with Minister of Cooperative Regulation No. 4 of 2024 and will ultimately increase the confidence of members and operational efficiency of cooperatives. Conclusion From the community service activities carried out in this cooperative that the management is easier to manage cooperatives by applying cooperative applications that are able to process data quickly and accurately and in accordance with the format in the Minister of Cooperative Regulation No. 4 of 2024 so that the function of accuracy and transparency can be achieved. This is proven in the case of the completion of the reporting can be completed within 2 days where before using the Cooperative Application the annual report submission was delivered for more than 3 months from the specified time.